Pendampingan Mahasiswa dalam Pengembangan Bisnis Digital - merina pratiwi; Gellysa Urva; Amiroel Oemara Syarief (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
namely students who have excellent managerial knowledge and innovative products. Students as business actors, both pioneering and micro-based, are hampered by the lack of digital knowledge of students in various uniqueness ranging from business models to customer experience. In addition, the lack of student knowledge in utilizing technology or digitalization. The purpose of this community service is to provide understanding and knowledge of digital business development including product and packaging development strategies, facilities and infrastructure, and promotion and marketing communication strategies. This community service activity was carried out using lecture and discussion methods. The results of this service are that some students have understood about attractive product packaging design and are trying to use the platform as a means of promotion according to the products produced. Through this service, it is hoped that students can continue to be entrepreneurs by innovating to create new products